Improvement in the pre-hospital care of recreational drug users through the development of club specific ambulance referral guidelines - Heather Kim; Moore Fionna; Chapman Kerry; Nicolaou Michelle; Huggett Denise; Alldus Graham; Greene Shaun L; Wood David M; Drake Nicola; Dargan Paul I (BMC, 2008)
Abstract Background Previously developed 'club guidelines' developed for club owners and promoters have tended to focus more on the legislative aspects of clubs, rather than the medical management of unwell clubbers within club environments. Despite this lack of guidance on the management of unwell clubbers, a significant proportion of clubs have 'club medic' rooms for managing these individuals. However, due to the lack of specific guidance on the training of staff working in these rooms and guidelines on when an ambulance should be called for an unwell clubber, there have been instances previously where clubbers have been inappropriately managed within the club environment, and often referred to hospital only after significant physiological derangement has occurred, thereby leading to an increased risk of morbidity and mortality. Methods We identified owners and promoters of local club venues within the catchment area of our Emergency Department and working jointly with them and other key stakeholders, in particular the London Ambulance Service and Metropolitan Police, identified strategies to improve pre-hospital care for clubbers who become unwell as a result of recreational drug use. These included developing guidelines detailing indications for ambulance transfer to hospital for clubbers with recreational drug toxicity and the training of club medic staff to use the guidelines Results Following the initial development of a pilot set of guidelines, an audit of their use identified training needed relating to the assessment of unwell clubbers with recreational drug toxicity and revisions required to the pilot version of the guidelines. After training related to the revised guidelines, all the club medic staff were confident in their ability to assess unwell clubbers with recreational drug toxicity, the use of the guidelines and also when to call an ambulance. Conclusion Working with key stakeholders in the local community, we have developed guidelines that can be used to improve the pre-hospital care of clubber unwell with recreational drug toxicity, and demonstrated that individuals with a variety of medical knowledge can be trained to use these guidelines. Wider dissemination of these guidelines, both regionally, nationally and potentially internationally, may help to reduce the pre-hospital morbidity and mortality associated with recreational drug toxicity encountered in club environments.